Pengaruh Kompetensi dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan pada Bagian Produksi di PT XYZ Otomotif Karawang - Ersa Mayang Sari; Suroso; Flora Patricia Anggela (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of competence and work environment on employee productivity at PT. XYZ Automotive Karawang, located in KarawangInternational Industrial City, either partially or simultaneously. The method applied is a quantitative method with 35 employees from the production department of PT. XYZ Automotive Karawang as the research sample, was selected using the saturated sampling method. The analysis uses a multiple linear regression model, and the F test and t test use a significance level of 5%. The research results show that there is a partial influence of competence on the productivity of PT employees. XYZ Automotive Karawang, with Ttable value (4,555 > 1,690 or Tcount > Ttable). However, there was no significant partial effect of the work environment on work productivity (0.025 < 1.690 or Tcount < Ttable). However, there is a simultaneous influence between the work environment and competence on work productivity, indicated by the high F value, namely 12,553 > 4,26. The influence of competency and work environment on PT employee productivity. XYZ Automotive Karawang was 0.440 or 44%, while the remaining 0.560 or 56% was influenced by additional variables not covered in this research.